2023
DOI: 10.7759/cureus.43774
|View full text |Cite
|
Sign up to set email alerts
|

A Swine Model of Neural Circuit Electromagnetic Fields: Effects of Immediate Electromagnetic Field Stimulation on Cortical Injury

James Brazdzionis,
Mohamed M Radwan,
Finosh Thankam
et al.

Abstract: Background Neurologic diseases have profound disability, mortality, and socioeconomic effects worldwide. Treatment of these disorders varies but is largely limited to unique factors associated with neural physiology. Early studies have evaluated alterations in electromagnetic fields (EMF) due to neural disorders with subsequent modulation of EMF as a potential treatment modality. Swine models have begun to be evaluated as translational models in this effect. Methods EMF measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In fact, the original investigation of the ability of this sensor to identify an EMF was in neonatal mice hippocampal cells with histological comparison [ 17 ]. Subsequent studies have identified an animal cortical impact model that demonstrated specific EMF changes corresponding to histological changes and biomarker changes for brain trauma [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the original investigation of the ability of this sensor to identify an EMF was in neonatal mice hippocampal cells with histological comparison [ 17 ]. Subsequent studies have identified an animal cortical impact model that demonstrated specific EMF changes corresponding to histological changes and biomarker changes for brain trauma [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Male Yucatan miniswine purchased from Premier BioSource (Romona, CA) and kept with 12 hours of light and dark cycle at a temperature range of 72°–74° F at the animal care facility of Western University of Health Sciences, Pomona CA were fed with the Mini-Pig Grower Diet (Test Diet # 5801) and water ad libitum . Brain injury was induced, and EMF was applied to one swine after 2 days post-TBI (hereafter swine 2), one swine just after injury (hereafter swine 3), and no EMF in one swine (hereafter swine 1) as described [ 6 8 ]. The tissues from the injured and non-injured sites were collected after the swine was euthanized.…”
Section: Methodsmentioning
confidence: 99%
“…Since dysregulated gene expression is associated with TBI and altered gene expression may have a diagnostic and therapeutic role [ 5 ], this pilot study was designed to delineate the differentially expressed genes after TBI and the effect of electromagnetic field (EMF) on gene expression profile. In a recently developed TBI swine model [ 6 8 ], we conducted the RNA sequencing using the tissue samples from the injured site and compared the expression profile with the non-injured site (contralateral hemisphere).…”
Section: Introductionmentioning
confidence: 99%
“…Animals were maintained on a normal diet with unrestricted access to water. TBI model and EMF application were done as described [ 26 - 28 ]. Three animals were extemporaneously used in this pilot study and all of them were subjected to mechanical impact to develop TBI.…”
Section: Methodsmentioning
confidence: 99%
“…Animal 2 received the EMF therapy two days after TBI induction (delayed approach) and animal 3 received the EMF 20 minutes following TBI induction (immediate approach). Electromagnetic therapeutic stimulation and signal detection were performed as previously described [ 26 - 28 ].…”
Section: Methodsmentioning
confidence: 99%